Covered versus uncovered metal stent for endoscopic drainage of a malignant distal biliary obstruction: Meta‐analysis. Issue 5 (17th March 2022) - Yamashita, Yasunobu; Tachikawa, Ayaka; Shimokawa, Toshio; Yamazaki, Hirofumi; Itonaga, Masahiro; Sakai, Yuji; Sugiyama, Harutoshi; Nakai, Yousuke; Tanaka, Kiyohito; Isayama, Hiroyuki; Kitano, Masayuki
Abstract : Objectives: The role of a covered vs. an uncovered self‐expandable metal stent (SEMS) for malignant distal biliary obstruction (MDBO) is not clear. This meta‐analysis compared the efficacy of covered vs. uncovered SEMS for patients with MDBO after endoscopic insertion. Methods: A systematic meta‐analysis of all relevant articles listed in PubMed, the Cochrane Library, and Google Scholar databases was performed. Fixed effects or random effects models were used to investigate pooled effects with 95% confidence intervals (CIs). Results: The meta‐analysis included 2358 patients from 12 eligible studies. Time to recurrent biliary obstruction (RBO) was significantly longer for covered SEMS (mean difference, 45.51 days; 95% CI 11.79–79.24). Although there was no significant difference in the RBO rate, subgroup analysis in pancreatic cancer occupying more than 90% (PC) revealed that the RBO rates were significantly lower for covered SEMS (odds ratio [OR] 0.43, 95% CI 0.25–0.74). Stent migration, sludge formation, and overgrowth were significantly more common with a covered SEMS (OR 7.92, 95% CI 4.01–15.64; OR 3.25, 95% CI 1.89–5.59; OR 2.03, 95% CI 1.20–3.43, respectively). The rate of ingrowth was significantly lower for covered SEMS. There was no significant difference in total procedure‐related adverse events between the two types of SEMS. Conclusions: A covered SEMS is superior to an uncovered SEMS with respect to prevention of RBO in patients with MDBO, particularly those caused by PC.